Database systems a practical approach to design, implementation, and management - Connolly, Thomas M.; Beg, Carolyn E. (Pearson Education, 2015)
This book is ideal for a one- or two-term course in database management or database design in an undergraduate or graduate level course. The methodology for relational Database Management Systems is presented in simple, step-by-step instructions in conjunction with a realistic worked example using three explicit phases -- conceptual, logical, and physical database design.